Penerapan pendidikan karakter melalui pendidikan ips di SD 05 Baringin - Nuria Arisma Arisma (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
Abstract The purpose of this study is to describe the implementation of character education in the social studies education of SDNI05 BaringinIand to explore the facilitators and hindrances in the process of character building of students. This research is qualitative research. The results are as follows: (1) Character education is carried out through curricular activities and extracurricular activities. (2) Implement character education and social studies instruction in learning spaces from teacher preparation to classroom conditioning including arriving at school on time to shake hands and I recite the Quran. including opening and closing classes. (3) Most sociology teachers adopt the classroom teaching method in character education teaching which does not maximize students' iresponseItoIthe implementation of character education. I(4) Factors conducive to the implementation of character education in which the principles taught in every classroom Capcentrian values ​​of school culture and the support and foundation of principals and teachers.